Finite element modeling optimization of wind turbine blades from an earthquake engineering perspective. (1st November 2020) - Ali, Ahmer; De Risi, Raffaele; Sextos, Anastasios
Highlights: Intermediate FE blade model, between a lumped mass and a complex 3D FEM approach. Realistic consideration of blades in numerical seismic assessments of wind turbines. Closed-form solution for simplified mechanical properties of wind turbine blades. An FEA-integrated GA optimization of blades for use in global FEM of wind turbines. Abstract: In a seismic assessment context, wind turbine blades are often excluded from numerical studies mainly due to their complex shape and lack of sufficient data. This tends to suppress their modal effect from the global dynamic response and can potentially influence the reliability of the seismic vulnerability of wind turbines, determined in a traditional manner, i.e., employing the lumped mass approach. This study aims to provide a closed-form solution for deriving the cross-sectional properties of a typical airfoil to further calculate the flapwise, edgewise, and torsional stiffness of a typical wind turbine blade. A genetic algorithm (GA)-based modeling optimization is performed to evaluate the geometric and material parameters that are representative of realistic blades. These parameters are used to achieve the target blade mass, stiffness, and frequencies. The proposed approach results in design solutions (DS) as different combinations of these parameters. Each DS leads to mechanical and modal characteristics that are equivalent for all blade configurations, such as blades with or without webs, with or without structural twist and varying pitch axis locations. These solutions are employed to develop the blades of the RNA in a wind turbine model to test the efficiency of the method. It is suggested that blades should be realistically considered for reliable seismic assessment of wind turbines.